Teaching South and Southeast Asian Art Multiethnicity, Cross-Racial Interaction, and Nationalism - Kim, Bokyung; Pyun, Kyunghee (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This volume challenges existing notions of what is "Indian," "Southeast Asian," and/or "South Asian" art to help educators present a more contextualized understanding of art in a globalized world. In doing so, it (re)examines how South or Southeast Asian art is being made, exhibited, circulated and experienced in new ways in the United States or in regions under its cultural hegemony. The essays presented in this book examine both historical and contemporary transformations or lived experiences of monuments and regional styles (sites) from South or Southeast Asian art in art making, subsequent usage, and exhibition-making under the rubric of "Indian," "South Asian," "or "Southeast Asian" Art. Bokyung Kim is Instructional Assistant Professor of Art History at the University of Mississippi, USA. Her current research involves several topics in the early interactions between Java (Indonesia) and the mainland of Southeast Asia. Kyunghee Pyun is Associate Professor of Art History at the Fashion Institute of Technology, State University of New York, USA. Her scholarship focuses on history of collecting, reception of Asian art and design, diaspora of Asian artists, and Asian American visual culture.
1. Unity and Multiculturalism: Pedagogical Context for South and Southeast Asian Art -- 2. Refuting Colonial Legacies: Many Lives of Ancient Khmer Sculpture: From Pre-Ankorian Period to Contemporary Cambodia -- 3. Locating Filipino Art in U.S. Museums: The Enduring Legacy of the 1904 Louisiana Purchase Exposition -- 4. Spirituality and Modern Art in India and the Himalayas: Neo-Tantra, Tibet, and the Goddess -- 5. The Role of Museums in Teaching the Art History of South and Southeast Asia -- 6. Politics of Public Art: Communities of Negotiation: Unity in Diversity: Teaching the Syncretistic Aspects of Ancient Indonesian Art from the 8th to the 15th Century -- 7. A Tale of Two Temples: The Rajarajeshvara Temple (c. 1010) in South India and the Sri Ganesha Temple (1990) in Nashville, TN -- 8. Beyond the Buddha Image: Buddhist Banners and the Art of Belief in Mainland Southeast Asia -- 9. Emerging Art of Bangladesh: Reshaping National History and Identity -- 10. Contested Cultural Identity: Building National Heritage: Gandhara Revisited: From Pamir to Uighur -- 11. Why Mughal Matters: Teaching Mughal Material in the Twenty-first Century -- 12. Rashtrapati Bhavan ("Presidential Palace") in New Delhi as Architecture of Authority: Teaching Difficult Heritages of Colonial Rule -- 13. Conclusion: How to Teach South and Southeast Asia in a Global Context. .
Keywords: Art -- Study and teaching; Teachers -- Training of; Southeast Asia -- History; Art -- History; Creativity and Arts Education; Teaching and Teacher Education; History of Southeast Asia; Art History